Lower cerebral blood flow is associated with impairment in multiple cognitive domains in Alzheimer's disease. Issue 5 (27th September 2016) - Leeuwis, Anna E.; Benedictus, Marije R.; Kuijer, Joost P.A.; Binnewijzend, Maja A.A.; Hooghiemstra, Astrid M.; Verfaillie, Sander C.J.; Koene, Teddy; Scheltens, Philip; Barkhof, Frederik; Prins, Niels D.; van der Flier, Wiesje M.
Abstract: Introduction: We examined the association between decreased cerebral blood flow (CBF) and cognitive impairment in Alzheimer's disease (AD), mild cognitive impairment (MCI), and subjective cognitive decline (SCD). Methods: We included 161 AD, 95 MCI, and 143 SCD patients from the Amsterdam Dementia Cohort. We used 3‐T pseudo‐continuous arterial spin labeling to estimate whole‐brain and regional partial volume–corrected CBF. Neuropsychological tests covered global cognition and five cognitive domains. Associations were investigated using linear regression analyses. Results: In the whole sample, reduced overall and regional CBF was associated with impairment in all cognitive domains. We found significant interactions between diagnosis and CBF for language and between diagnosis and parietal CBF for global cognition and executive functioning. Stratification showed that decreased CBF was associated with worse performance in AD patients but not in MCI or SCD. Discussion: Our results suggest that CBF may have potential as a functional marker of disease severity.